Conflict Sensitive Water Supply : Lessons from Operations - Ruckstuhl, Sandra (World Bank, Washington, DC, 2017)
Water, as a resource, is integral to human activities of all kinds. The water sector, as a society's means of ensuring individuals have sufficient water is fundamental to recovery and development. While designing and implementing water supply operations in any societal context is a complicated endeavor, doing so in contexts affected by conflict, fragility and violence is inherently associated with compounded challenges. The objective of this study is to summarize operational lessons from task teams to inform effective water supply and access operations in conflict-affected and fragile situations. This paper defines common operational challenges and describes actions that task teams have taken in Bank projects in order to address those challenges. Further, the paper explores ways to ensure that water supply projects in fragile and conflict-affected situations (FCS) contexts, in addition to achieving technical objectives, can also address perpetual causes of conflict and fragility. The risks of escalating violence and decreasing stability are exacerbated in situations where access to water resources and services is poor, constrained, inequitable, and unsustainable. This knowledge product summarizes lessons from World Bank task teams that have prepared and implemented water supply projects in locations affected by conflict, fragility and violence. The findings intend to support operational problem-solving during water operations that are conducted in these situations. The study engaged task team members and surveyed project documentation, consolidating data on contextual and operational challenges and responsive methods that staff recommend. The findings of this study show that clear priorities in process and organizational capacity, with a focus on access, are needed to ensure that water supply operations in FCS contexts are conflict-sensitive.